태국의 불교사찰 벽화에 관한 연구 - 노장서; Jang Suh Noh (SUVANNABHUMI, 1(2), 2009)
This research tries to review the history and concepts of Thai temple mural painting. According to the research results, the history of Thai mural painting dates back to the late 14th century when Wat Chedi Chet Taeo in Si Satchanalai was built. The Sinhalese elements embedded in the Sukhothai murals are also found in the Ayuthayan stupa murals made in the early 15th century. The mid 18th century's Burmese invasion into Ayuthaya destroyed most of Buddhist temples in the Kingdom of Ayuthaya and as a result, Buddhist murals of the late Ayuthayan age are hardly found except for some temple murals located outside of the capital. The late Ayuthayan murals are much different from the early Ayuthayan murals in that they are narrative in depicting Jataka and the life of Lord Buddha. This classical mural painting culminated in the age of Rama III of Bangkok Dynasty. His successor Rama IV undertook westernized reforms which influenced the area of traditional mural painting. Consequently, new western style Buddhist mural paintings were produced while themes of mural painting were enlarged to the other subjects such as historical recording of royal and social events. This trend continued in the age of Rama V but the development of Thai Buddhist mural painting discontinued after the death of Rama V due to the rapid westernization and decrease of illiteracy. The existing Buddhist murals produced on or before the reign of Rama V are deteriorating and disappearing. The reasons for this are partly because of Thailand's humid climate. However, some social backgrounds such as the lack of concern for preserving old Buddhist murals can not be disregarded. Considering the substantial value of Thai Buddhist murals as a cultural resource in Thai society, it is very urgent to establish appropriate conservation policy for them.